SILVIELLA, NEW GENUS OF PHYLLOBAENINAE (COLEOPTERA, CLERIDAE) FROM THE SOUTHERN PART OF SOUTH AMERICA (Acta Entomológica Chilena, 2022)
A new genus is created to receive lwo species segregated from Eurymetopum Blanchard, 1844 and a newone. A study of the type material of all the laxa included was made. Species are characterized on the basisof exlernal morphology, coloration and the structure of the male and female genitalia, using seríes ofmaterial representing their entire distributional ranges. Descriptions are accompanied by figures of thespecies and their characters of taxonomical valué. A key is provided and geographical distributions aremaped.
Keywords: Taxonomía, Nuevo género, Phyllobaeninae Cleridae, Coleóptera, Chile-Argentina